Porous carbon / primary graphite composite granulated fast-charging graphite material and preparation method thereof

The fast-charge graphite material preparation method through porous carbon/primary graphite composite granulation, combined with the high capacity of porous carbon and the long cycle performance of graphite, and the first-effect and rate performance of the material are improved by asphalt coating, the existing graphite negative electrode is solved. The problem of material degradation in lithium-ion batteries achieves high efficiency, long life and high magnification battery performance.

CN119430170APending Publication Date: 2025-02-14SHANGHAI GLENN FUTURE MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411513528.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing graphite negative electrode materials have degraded battery performance due to structural defects and surface side reactions during the circulation of lithium-ion batteries, especially in terms of fast charging rate performance, cycle life and energy density.

Method used

The fast-charge graphite material of porous carbon/primary graphite composite granulation is used to prepare the material through steps such as dry mixing of physical powder, premixing asphalt, heating softening, asphalt coating and carbonization molding. This method combines the high capacity of porous carbon and the long cycle performance of graphite, and improves the first-effect and rate-efficiency performance of the material through asphalt coating.

Benefits of technology

It improves the fast charging performance, cycle life and energy density of lithium-ion batteries, reduces the cost and production difficulty of materials, and is suitable for commercial production applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a porous carbon / primary graphite composite granulated fast-charging graphite material and a preparation method thereof, composite granulation is carried out according to a certain proportion, under the coating of outer layer compact asphalt, porous carbon is responsible for the storage of high-capacity and high-concentration lithium ions, and a graphite body is responsible for the long circulation effect. Simply, the coated asphalt is responsible for high first efficiency, the inner-layer porous carbon is responsible for high capacity and high rate performance, and the graphite body ensures long cycle performance. Wherein the porous carbon has the lowest order degree, the graphite has the highest order degree, the coated asphalt is between the porous carbon and the graphite, and the porous carbon, the graphite and the coated asphalt are combined together to construct high-first-effect, long-cycle and high-rate fast-charging graphite performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of graphite material preparation, and specifically relates to a porous carbon / primary graphite composite granulated fast-filling graphite material and a preparation method thereof. Background Art

[0002] With the rapid development of new energy vehicles, energy storage market and fast-moving consumer electronics, the demand for lithium-ion products has exploded. Driven by the combined development of power batteries, energy storage batteries and consumer batteries, the market demand for coated asphalt materials used in the modification of negative electrode materials for lithium-ion batteries has increased significantly, and will continue to grow until at least 2030. At present, natural graphite, as a negative electrode material for lithium-ion batteries, will continue to consume active lithium during the battery cycle due to structural defects and more surface side reactions, resulting in a certain degree of decline in battery cycle life performance, fast charge rate performance, energy density performance and first efficiency.

[0003] Improving the fast charging performance of graphite negative electrode materials is very necessary for the commercial application of lithium batteries. Therefore, in recent years, researchers have adopted a variety of means to improve the fast charging ability of graphite negative electrodes. From a theoretical point of view, there are probably two ways to improve the fast charging performance of graphite: enhancing the diffusion rate of bulk active materials and improving the interface dynamics of bulk materials. Enhancing the single-phase diffusion of bulk active materials refers to improving the diffusion rate of lithium ions between active lithium storage particles and the sheet transmission rate within graphite. Improving interface dynamics means accelerating the desolvation of lithium ions and improving the migration ability of lithium ions in the SEI film on the surface of active materials. Generally speaking, commonly used effective strategies include adjusting the solvation composition and structure of the electrolyte, adding specific film-forming agents to the electrolyte, structural modification at the graphite boundary, designing the particle ratio of graphite bulk materials, optimizing the electrolyte composition (low viscosity electrolyte), optimizing the charging strategy, etc. Through the flexible application of these strategies, commercial battery factories have developed a series of high-performance graphite negative electrodes, which provide important reference for industrial production.

[0004] Recent research focuses on pre-coating thin polymers, inorganic compounds, and mixed organic / inorganic layers on the surface of graphite particles. These surface coating strategies can effectively inhibit electrolyte decomposition, improve initial Coulombic efficiency, and reduce irreversible capacity loss. In addition, the artificial coating layer can act as a sifter for lithium ions and solvent molecules, accelerating the desolvation of lithium ions, ensuring the rapid passage of lithium ions while avoiding the destruction of the graphite structure by the co-embedding of solvent molecules. Therefore, researchers have conducted in-depth studies on the physicochemical properties of various coatings and the protection mechanisms for graphite electrodes.

[0005] Modifying the graphite negative electrode body can enhance the lithium ion storage concentration and diffusion capacity inside the graphite and improve the intrinsic ionic conductivity of graphite. Since graphite is a two-dimensional structural material with layered arrangement, the migration of lithium ions in graphite is highly anisotropic. The diffusion coefficient of lithium ions in the direction perpendicular to the graphite sheet is much lower than that at the edge plane, and must reach the edge of the graphite sheet through a long migration path. Therefore, for the fast-charging oriented modification of graphite, another effective strategy is to enhance the active sites of the reaction between graphite and lithium ions through micromorphology design and structural improvement, and enhance electron transmission, thereby improving the fast-charging performance.

[0006] The current bulk modification method can effectively improve the fast charging performance of graphite. However, structural design and increase of active sites for graphite are not suitable for commercial production applications. For the microstructural design of graphite, the microstructural design of the current design products is launched on the basis of balancing capacity, first effect, cycle and cost, and the room for improvement in microstructural design is limited. As for the active sites of the reaction between graphite and lithium ions, it is necessary to regulate the granulation and graphitization processes, and even increase the number of processes, which brings certain difficulties and cost increases to industrial mass production. Therefore, it is urgent to develop new methods to improve fast charging. Summary of the invention

[0007] The object of the present invention is to provide a porous carbon / primary graphite composite granulated fast-filling graphite material and a preparation method thereof, so as to solve one or more of the above-mentioned prior art problems.

[0008] On the one hand, the present invention provides a method for preparing a porous carbon / primary graphite composite granulated fast-filling graphite material, comprising the following steps:

[0009] Material dry mixing: Physically dry mixing the crushed primary graphite powder particles with the porous carbon powder particles to obtain a mixed material;

[0010] Asphalt premixing: The mixture is subjected to a second coating treatment, wherein the mixture powder particles are premixed with the asphalt powder particles;

[0011] Heating and softening: heating the mixture in a high temperature fusion granulator at a heating rate of 0.1-10°C / min, preferably 1-8°C / min, more preferably 3-6°C / min, to 270-350°C, preferably 280-320°C, more preferably 280-300°C, and keeping the temperature for 10-480min, preferably 30-360min, more preferably 60-240min, to ensure the fluidity of the asphalt;

[0012] Asphalt coating: The above materials are vacuumed in a high-temperature fusion granulator, stirred, mixed, granulated and coated, and spheroidized;

[0013] Carbonization molding: In a nitrogen atmosphere, the temperature is raised to 600-1500°C, preferably 800-1400°C, more preferably 800-1200°C, and the double-layer coated graphite is subjected to constant temperature carbonization treatment for a holding time of 60-800min, preferably 120-840min, more preferably 240-720min, to obtain the fast-filling graphite material.

[0014] In some embodiments, the graphite is selected from artificial graphite, natural graphite, graphite microcrystals and other graphite-like carbon materials.

[0015] In some embodiments, the graphite particle size is 6-44 μm, preferably, the graphite particle size is 8-25 μm, more preferably, the graphite particle size is 12-16 μm, and the BET specific surface area of ​​the porous carbon is 100-3000 m 2 / g, the pore size D50 is 0.5-50nm, preferably, the BET specific surface area of ​​the porous carbon is 500-2000m 2 / g, pore size D50 = 2-36nm, more preferably, the BET specific surface area of ​​the porous carbon is 800-1200m 2 / g, pore size D50 = 4-32nm.

[0016] In some embodiments, the mass ratio of the graphite and the porous carbon mixture is 80:(2-40), preferably, the mass ratio of the graphite and the porous carbon mixture is 80:(4-30), and more preferably, the mass ratio of the graphite and the porous carbon mixture is 80:(8-25).

[0017] In some embodiments, the asphalt particle size is 5-30μm, preferably, the asphalt particle size is 6-22μm, more preferably, the asphalt particle size is 8-14μm, the asphalt softening point is 120-250℃, preferably, the asphalt softening point is 140-240℃, more preferably, the asphalt softening point is 160-250℃, the residual carbon value of the asphalt is 10%-60%, preferably, the residual carbon value of the asphalt is 130%-45%, more preferably, the residual carbon value of the asphalt is 35%-40%, the asphalt TI-QS content is 1%-30%, preferably, the asphalt TI-QS content is 3%-25%, more preferably, the asphalt TI-QS content is 5%-20%.

[0018] In some embodiments, the mass ratio of the mixture powder particles to the asphalt powder particles is 100:(2-22), preferably, the mass ratio of the mixture powder particles to the asphalt powder particles is 100:(4-18), and more preferably, the mass ratio of the mixture powder particles to the asphalt powder particles is 100:(4-14).

[0019] In some embodiments, the vacuum degree of the vacuum pumping is 0-1 bar, preferably, the vacuum degree of the vacuum pumping is 0.5-0.99 bar, and more preferably, the vacuum degree of the vacuum pumping is 0.9-0.98 bar.

[0020] In some embodiments, the flow rate of the nitrogen gas is 0.1-5 L / min, preferably, the flow rate of the nitrogen gas is 0.2-2 L / min, and more preferably, the flow rate of the nitrogen gas is 0.25-1 L / min.

[0021] On the other hand, the present invention provides a porous carbon / primary graphite composite granulated fast-filling graphite material obtained by the above method.

[0022] In another aspect, the present invention provides a button battery, comprising the porous carbon / primary graphite composite granulated fast-charging graphite material obtained by the above preparation method.

[0023] The specific button cell assembly method is as follows: the graphite sample is mixed with Super C and polyvinylidene fluoride (PVDF) at a mass ratio of 95.5:2.5:2.0, and a uniform slurry is formed with N-methylpyrrolidone (NMP) and then coated on a copper foil, and dried at 80°C for 12 hours to serve as a working electrode. A metal lithium sheet is used as the counter electrode, and Celgard 2500 is used as the diaphragm to assemble a CR2016 button half-cell, in which the electrolyte is 1 mol·L -1 LiPF6 was dissolved in ethylene carbonate (EC) / dimethyl carbonate (DMC) / ethyl methyl carbonate (EMC) (volume ratio 1:1:1), and each battery used 4×10 -2 mL of electrolyte and assembled in a glove box filled with Ar.

[0024] The method for preparing the spray protective tape of the present invention has the following advantages:

[0025] The solution proposed in the article is: porous carbon particles + primary graphite particles are composited and granulated in a certain proportion. Under the outer layer of dense asphalt coating, the porous carbon is responsible for the storage of high-capacity and high-concentration lithium ions, and the graphite body is responsible for the long cycle effect. Simply put, the coated asphalt is responsible for high first efficiency, the inner layer of porous carbon is responsible for high capacity and high-rate performance, and the graphite body guarantees long cycle performance. Among them, the porous carbon has the lowest order, the graphite has the highest, and the coated asphalt is between the two. The combination of the three constructs a fast-charging graphite performance with high first efficiency, long cycle, and high rate. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with the examples. The following examples are only used to more clearly illustrate the performance of the present invention, and are not limited to the following examples.

[0027] Embodiment 1:

[0028] 1. Material dry mixing. Physically dry mix 80g of crushed primary graphite (particle size D50 = 16μm, artificial graphite) powder particles with 20g of porous carbon (specific surface area 1200m2 / g, pore size D50 = 2nm) powder particles to obtain a mixed material;

[0029] 2. Asphalt premixing. The mixture is subjected to a second coating treatment. 100g of the mixture powder particles are premixed with 10g of asphalt powder particles with a softening point of 250°C (residual carbon 71%, TI-QS component ≥ 8%);

[0030] 3. Heating and softening. Heat the mixture in a high-temperature fusion granulator at 5°C / min to 300°C and maintain for 180 minutes to ensure the fluidity of the asphalt;

[0031] 4. Asphalt coating. The above materials are placed in a high-temperature fusion granulator, vacuumed to a negative pressure of 0.99 bar, stirred, mixed, granulated and coated, and spheroidized;

[0032] 5. Carbonization molding. In a 0.25L / min nitrogen atmosphere, the temperature is raised at a rate of 5°C / min to 1300°C, and the double-layer coated graphite is carbonized at a constant temperature for 720min to obtain a fast-filling graphite material;

[0033] 6. Carry out the preparation of the buckling electrode to obtain the buckling electrode of the graphite material.

[0034] Example 2

[0035] On the basis of Example 1, artificial graphite is replaced by natural graphite.

[0036] Example 3

[0037] On the basis of Example 1, the artificial graphite is replaced by microcrystalline graphite.

[0038] Example 4

[0039] Based on Example 1, the artificial graphite particle size D50=8 μm.

[0040] Example 5

[0041] Based on Example 1, the artificial graphite particle size D50=28 μm.

[0042] Example 6

[0043] Based on Example 1, the porous carbon BET value is 100m 2 / g, pore diameter D50 = 1.2 μm.

[0044] Example 7

[0045] Based on Example 1, the porous carbon BET value is 3000m 2 / g, pore diameter D50 = 2nm.

[0046] Example 8

[0047] Based on Example 1, the mixing ratio of graphite and porous carbon is 90:10.

[0048] Example 9

[0049] Based on Example 1, the mixing ratio of graphite and porous carbon is 60:40.

[0050] Example 10

[0051] Based on Example 1, the mixing ratio of graphite and asphalt is 100:2.

[0052] Embodiment 11

[0053] Based on Example 1, the mixing ratio of graphite and asphalt is 100:15.

[0054] Example 12

[0055] Based on Example 1, in step 3, the temperature is further increased to 200° C. at a heating rate of 1° C. / min and maintained at this temperature for 30 min.

[0056] Embodiment 13

[0057] Based on Example 1, the temperature in step 3 was further increased to 300°C at a heating rate of 10°C / min.

[0058] Embodiment 14

[0059] On the basis of Example 1, the vacuum degree in step 4 is 0 bar, and in step 5 the temperature is further raised to 400° C. and kept constant at this temperature for 120 min.

[0060] Embodiment 15

[0061] On the basis of Example 1, the vacuum degree in step 4 is 0.99 bar, and in step 5 the temperature is further raised to 1500° C. and kept constant at this temperature for 700 min.

[0062] Comparative Example 1

[0063] The same as the scheme of Example 1, except that porous carbon is not added.

[0064] Comparative Example 2

[0065] The same as the scheme of Example 1, except that the artificial graphite is not coated with asphalt.

[0066] Performance Testing:

[0067] Button battery assembly:

[0068] The graphite sample was mixed with Super C and polyvinylidene fluoride (PVDF) in a mass ratio of 95.5:2.5:2.0, and a uniform slurry was formed with N-methylpyrrolidone (NMP) and then coated on a copper foil. After drying at 80°C for 12 hours, it was used as a working electrode. A metal lithium sheet was used as the counter electrode, and Celgard 2500 was used as the diaphragm to assemble a CR2016 button half-cell, in which the electrolyte was 1 mol·L -1 LiPF6 was dissolved in ethylene carbonate (EC) / dimethyl carbonate (DMC) / ethyl methyl carbonate (EMC) (volume ratio 1:1:1), and each battery used 4×10 -2 mL of electrolyte and assembled in a glove box filled with Ar.

[0069] Test charge and discharge conditions: In the range of 0-2.0V, first use 0.1C constant current to 2.0V, then use constant voltage 2.0V until the current is less than 0.02C. After 2 cycles, change to 1.0CC / 1.0CD. After 50 cycles, remove the power button.

[0070] Rate test: The battery is tested for rate discharge performance at different current densities (1.0C, 2C, 3C, 5C, 6C, 8C). First, the battery cell is fully charged at 1C (0-2.0V), and then discharged after standing for 30 minutes, with a cut-off voltage of 2.0V.

[0071] The experimental results are shown in the following table:

[0072]

[0073]

[0074] As can be seen from the table above, after the porous carbon is added, the composite negative electrode is coated, while ensuring that the material's gram capacity and first efficiency do not decrease, the material's rate is improved and increased. The greater the ratio of the mixture of graphite and porous carbon, the higher the order, and the closer the cycle performance is to the graphite itself; the smaller the ratio of the mixture of graphite and porous carbon, the lower the order, and the higher the rate. With the effect of asphalt coating, the first efficiency and capacity are guaranteed to a certain extent, and the β component in the asphalt cannot be too low, otherwise the bonding effect between the graphites is too poor, the conductivity is poor, and the internal resistance is too large to affect the rate.

[0075] The above description is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this field, several modifications and improvements can be made without departing from the creative concept of the present invention, and these should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing a porous carbon / primary graphite composite granulated fast-filling graphite material, characterized in that: The following steps are involved: Material dry mixing: Physically dry mixing the crushed primary graphite powder particles with the porous carbon powder particles to obtain a mixed material; Asphalt premixing: The mixture is subjected to a second coating treatment, wherein the mixture powder particles are premixed with the asphalt powder particles; Heating and softening: heating the mixture in a high temperature fusion granulator at a heating rate of 0.1-10°C / min, preferably 1-8°C / min, more preferably 3-6°C / min, to 270-350°C, preferably 280-320°C, more preferably 280-300°C, and keeping the temperature for 10-480min, preferably 30-360min, more preferably 60-240min, to ensure the fluidity of the asphalt; Asphalt coating: The above materials are vacuumed in a high-temperature fusion granulator, stirred, mixed, granulated and coated, and spheroidized; Carbonization molding: In a nitrogen atmosphere, the temperature is raised to 600-1500°C, preferably 800-1400°C, more preferably 800-1200°C, and the double-layer coated graphite is subjected to constant temperature carbonization treatment for a holding time of 60-800min, preferably 120-840min, more preferably 240-720min, to obtain the fast-filling graphite material.

2. The preparation method according to claim 1, characterized in that: The graphite is selected from one of other graphite-like carbon materials such as artificial graphite, natural graphite and graphite microcrystals.

3. The preparation method according to claim 1, characterized in that: The graphite particle size is 6-44 μm, preferably, the graphite particle size is 8-25 μm, more preferably, the graphite particle size is 12-16 μm, and the BET specific surface area of ​​the porous carbon is 100-3000 m 2 / g, the pore size D50 is 0.5-50nm, preferably, the BET specific surface area of ​​the porous carbon is 500-2000m 2 / g, pore size D50 = 2-36nm, more preferably, the BET specific surface area of ​​the porous carbon is 800-1200m 2 / g, pore size D50 = 4-32nm.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the graphite and the porous carbon mixture is 80:(2-40), preferably, the mass ratio of the graphite and the porous carbon mixture is 80:(4-30), and more preferably, the mass ratio of the graphite and the porous carbon mixture is 80:(8-25).

5. The preparation method according to claim 1, characterized in that: The asphalt particle size is 5-30μm, preferably, the asphalt particle size is 6-22μm, more preferably, the asphalt particle size is 8-14μm, the asphalt softening point is 120-250℃, preferably, the asphalt softening point is 140-240℃, more preferably, the asphalt softening point is 160-250℃, the residual carbon value of the asphalt is 10%-60%, preferably, the residual carbon value of the asphalt is 130%-45%, more preferably, the residual carbon value of the asphalt is 35%-40%, the asphalt TI-QS content is 1%-30%, preferably, the asphalt TI-QS content is 3%-25%, more preferably, the asphalt TI-QS content is 5%-20%.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the mixed powder particles to the asphalt powder particles is 100:(2-22), preferably, the mass ratio of the mixed powder particles to the asphalt powder particles is 100:(4-18), and more preferably, the mass ratio of the mixed powder particles to the asphalt powder particles is 100:(4-14).

7. The preparation method according to claim 1, characterized in that: The vacuum degree of the vacuum pumping is 0-1 bar, preferably, the vacuum degree of the vacuum pumping is 0.5-0.99 bar, and more preferably, the vacuum degree of the vacuum pumping is 0.9-0.98 bar.

8. The preparation method according to claim 1, characterized in that: The flow rate of the nitrogen gas is 0.1-5 L / min, preferably, the flow rate of the nitrogen gas is 0.2-2 L / min, and more preferably, the flow rate of the nitrogen gas is 0.25-1 L / min.

9. A quick-filling graphite material of porous carbon / primary graphite composite granulation obtained by the preparation method according to any one of claims 1 to 8.

10. A button battery comprising a fast-charging graphite material of porous carbon / primary graphite composite granulation obtained by the preparation method according to any one of claims 1 to 8.